Collision Tumor of the Clivus: Chordoma and Chronic Lymphocytic Leukemia. Case report and literature review - Yasuda, Marcos Ezequiel; Hart, Shannon; Lu, Jian-Qiang; Algird, Almunder (Journal of Neurological Surgery Part A: Central European Neurosurgery)
INTRODUCTION Collision tumours, defined as the simultaneous occurrence of two distinct neoplasms within the same anatomical location, are exceptionally rare in the clivus. The coexistence of chordoma and chronic lymphocytic leukemia (CLL) within the clivus has not been previously reported, making this case particularly noteworthy. CLINICAL PRESENTATION: We present the case of a 69-year-old woman with a known history of stable CLL who presented with a 3-month history of progressive right-sided horizontal diplopia and hemianopsia. Imaging revealed a large sellar/suprasellar lesion with significant involvement of both cavernous sinuses, prompting surgical intervention. An endoscopic endonasal transsphenoidal and transclival approach was utilized to achieve near-total mass resection, with a small remnant left in the right cavernous sinus due to its proximity to the internal carotid artery. Histopathological examination confirmed the presence of a collision tumour composed of chordoma and CLL. CONCLUSION: This case represents the first reported instance of a collision tumor involving a chordoma and CLL within the clivus. The patient’s postoperative course was uneventful, and she remains stable at 3-month follow-up after receiving adjuvant radiotherapy. The rarity of such a collision tumor underscores the need for heightened clinical suspicion and thorough pathological evaluation in cases presenting with atypical skull base lesions. The involvement of a multidisciplinary team was crucial in the management and favorable outcome of this complex case.